2015
DOI: 10.18632/oncotarget.3955
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of CaMKII in cancer

Abstract: Ca2+/calmodulin-dependent protein kinase II (CaMKII) is a multifunctional serine/threonine kinases best known for its critical role in learning and memory. Recent studies suggested that high levels of CaMKII also expressed in variety of malignant diseases. In this review, we focus on the structure and biology properties of CaMKII, including the role of CaMKII in the regulation of cancer progression and therapy response. We also describe the role of CaMKII in the diagnosis of different kinds of cancer and recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 76 publications
2
70
0
2
Order By: Relevance
“…CaMKII holoenzymes contain 8-14 subunits, each with a catalytic domain, a regulatory domain, and an association domain, all organized so that catalytic domains are placed in pairs. [67][68][69][70] Ca 2C /CaM binding to the regulatory domain causes a conformational change that removes the autoinhibitory pseudosubstrate segment from the active site, which allows for ATP binding and also exposes T286 of the autoinhibitory pseudo-substrate segment for phosphorylation. 69,[71][72][73][74][75] This phosphorylation sterically prevents the inhibitory segment from returning to the active site once Ca 2C /CaM has dissociated, resulting in continued activation independent of calcium.…”
Section: Molecular Regulation Of Epithelial Scattering By Calcium/calmentioning
confidence: 99%
“…CaMKII holoenzymes contain 8-14 subunits, each with a catalytic domain, a regulatory domain, and an association domain, all organized so that catalytic domains are placed in pairs. [67][68][69][70] Ca 2C /CaM binding to the regulatory domain causes a conformational change that removes the autoinhibitory pseudosubstrate segment from the active site, which allows for ATP binding and also exposes T286 of the autoinhibitory pseudo-substrate segment for phosphorylation. 69,[71][72][73][74][75] This phosphorylation sterically prevents the inhibitory segment from returning to the active site once Ca 2C /CaM has dissociated, resulting in continued activation independent of calcium.…”
Section: Molecular Regulation Of Epithelial Scattering By Calcium/calmentioning
confidence: 99%
“…Accumulating evidence has also shown that CaM plays a pivotal role in tumor development. 14,15 In addition, it has been reported that Ī³ isoform of CaMKII (CaMKIIĪ³) is required for maintenance of stem-like and tumorigenic properties of lung and liver cancer cells. 12,13 Among them, Ca 2+ /CaM-dependent protein kinase II (CaMKII), a serine/threonine kinase, directly or indirectly upregulates multiple signaling pathways, such as extracellular signal-regulated kinase (ERK)1/2, protein kinase B (Akt), signal transducer and activator of transcription 3 (Stat3), and Ī²-catenin, which are responsible for cancer cell proliferation and metastasis.…”
mentioning
confidence: 99%
“…AKT1 is involved in cell proliferation and survival [25], while CAMK2D, a member of the CAMK family, activates cancer cell proliferarion [26]. In fact, CRK proteins have been reported to be dysregulated in several human malignancies [27].…”
Section: Discussionmentioning
confidence: 99%